Revisão taxonômica e análise filogenética de Scopogonalia Young, 1977 com a descrição de uma espécie nova do grupo externo - Leal, Afonso henrique (2014)
The genus Scopogonalia Young belongs to the family Cicadellidae, subfamily Cicadellinae and tribe Cicadellini and contains 11 species, all recorded in South America: S. subolivacea (Stål) (type species), S. interruptula (Osborn), S. echinura Young, S. golbachi Young, S. nargena Young, S. oglobini Young, S. paula Young, S. penicula Young, S. altmanni Cavichioli, S. plaumanni Cavichioli, and S. splendida Cavichioli. In this work, Scopogonalia and two of its species are redescribed, as well as six new ones are described, which of them five from specimens from Brazil and one from Argentina. Moreover a phylogenetic analysis of the genus is conducted to test its monophyly and propose a hypothesis of phylogenetic relationship between them. The terminal taxa of the phylogenetic analysis are all species of Scopogonalia and six outgroup taxa: Tretogonia cribrata Melichar, Cyclogonia caeligutata Mejdalani & Nessimian, Rotigonalia larissae Cavichioli, Rotigonalia olivacea Cavichioli, Plerogonalia rudicula (Jacobi), and a new species of Rotigonalia which is also described. A taxonomic key of Scopogonalia and another of Rotigonalia were elaborated. 59 morphological and color pattern characters were used, identified based on topographic criteria, which of them the multistate were coded as unordered and the uninformative autopomorphic were included. The maximum parsimony analysis was conducted with the software TNT, resulting in 8 most parsimonious trees, with length = 137, consistency index (CI) = 0.47 (excluding uninformative characters), and retention index (RI) = 0.72. In all of them, Scopogonalia is monophyletic, although with low support, having as unambiguous sinapomorphies the reversion of the clypeus from swollen to not swollen, the first condition present in Rotigonalia and Plerogonalia, and the opening of the bases of the median and internal anteapical cell of the forewings. An implied weighting analysis lead to three trees, all included in the original ones, which the strict consensus shows little conflict. One of the clades supports a previous connection between the core area of the Cerrado biome and savanna enclaves in tha Amazon and Atlantic Forest biomes. Another one strengthens a proposed relationship between the central and south blocks of areas of endeminsm of the Atlantic Forest.